2021
DOI: 10.1002/ana.26263
|View full text |Cite
|
Sign up to set email alerts
|

miR‐146b Protects the Perinatal Brain against Microglia‐Induced Hypomyelination

Abstract: In the premature newborn, perinatal inflammation mediated by microglia contributes significantly to neurodevelopmental injuries including white matter injury (WMI). Brain inflammation alters development through neuroinflammatory processes mediated by activation of homeostatic microglia toward a pro-inflammatory and neurotoxic phenotype. Investigating immune regulators of microglial activation is crucial to find effective strategies to prevent and treat WMI. Methods: Ex vivo microglial cultures and a mouse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 71 publications
3
36
0
Order By: Relevance
“…By contrast, the cerebellum appears to be particularly sensitive to systemic inflammation during the perinatal period. where (Bokobza et al, 2022;Van Steenwinckel et al, 2019;Veerasammy et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the cerebellum appears to be particularly sensitive to systemic inflammation during the perinatal period. where (Bokobza et al, 2022;Van Steenwinckel et al, 2019;Veerasammy et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have shown that electro acupuncture-stimulated hippocampal neurogenesis in the rat model of focal cerebral ischemia and reperfusion was associated with an increased miR-146b expression, while inhibition of miR-146b reduced stimulatory effect of acupuncture on the hippocampal neurogenesis [75]. It should be noted that, aside from the novel neuronal functions of miR-146b described in our study, miR-146b is expressed in microglial cells and is involved in the negative regulation of neuroinflammation [25,27]. Previous studies have demonstrated that focal cerebral ischemia and reperfusion can induce inflammation and that acupuncture is able to reduce neuroinflammation [76].…”
Section: Discussionmentioning
confidence: 44%
“…As previously miR-146b had been shown to regulate immune responses in variety of cells and tissues [15,17,27], and because microglia can control adult neurogenesis through secretion of various soluble factors including cytokines [68,69], we studied in more detail the morphology of microglia cells. We did not observe signs of microglial activation in Mir146b-/mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations